Value Sensitive Design and power in socio-technical ecosystems - Mattis Jacobs; Christian Kurtz; Judith Simon; Tilo Böhmann (Internet Policy Review, 2021)
Recent European policy papers call for the consideration of human values in the design of information technology. Value Sensitive Design (VSD) provides a framework for systematically accounting for values in the design of technical artefacts. This paper examines how the distribution of power within socio-technical ecosystems poses a challenge for the application of VSD. It identifies four crucial factors determining the effect of the distribution of power on VSD: the level of decentralisation of the ecosystem; if VSD is applied at the core or periphery; when power can be exercised (temporality); and the phase of VSD (conceptual, empirical, and technical) that power can be exercised in. Based on these factors, it outlines how the challenge of accounting for power can be addressed.
Keywords: 300; Value sensitive design; Power; Sociotechnical ecosystems; Platforms; Blockchain